The Effect of Google Sites-Based Reproductive Health Learning on Knowledge, Attitudes, and Behaviors in Students - Ainun Mardia HM; Andi Asmawati Azis; Rachmawaty; Firdaus Daud; A. Mushawwir Taiyeb (Postgraduate, University of Mataram, 2026)
This study aims to examine the effect of Google Sites–based reproductive health education on students’ knowledge, attitudes, and behaviors. A quantitative quasi-experimental design with a pretest–posttest control group was employed. The sample consisted of 60 eleventh-grade students divided into two groups of 30 students each. The experimental group received reproductive health instruction using a Google Sites–based deep learning approach, while the control group received the same approach without Google Sites. Data were collected using a multiple-choice test (knowledge) and Likert-scale questionnaires (attitudes and behaviors), and analyzed using Independent Sample t-tests. Results showed significant differences between groups (p = 0.001). The experimental group demonstrated higher improvements: knowledge increased from 47.07 to 82.93 (76.2%), compared to 41.20 to 58.93 (43.0%) in the control group; attitudes increased from 61.07 to 89.27 (46.2%), compared to 48.40 to 70.50 (45.7%); and behaviors increased from 61.03 to 86.07 (41.0%), compared to 60.27 to 66.20 (9.8%). These findings indicate that integrating Google Sites as a digital learning medium enhances engagement and learning outcomes. In conclusion, Google Sites–based instruction is an effective strategy for improving students’ reproductive health knowledge, fostering positive attitudes, and promoting healthier behaviors.